2023
DOI: 10.1002/smll.202307132
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Oxidation Strategy Transforming Waste Foam to Hard Carbon Anodes for Boosting Sodium Storage Performance

Yuefang Chen,
Heyi Sun,
Xiang‐Xi He
et al.

Abstract: Large reserves, high capacity, and low cost are the core competitiveness of disordered carbon materials as excellent anode materials for sodium‐ion batteries (SIBs). And the existence and improper treatment of a large number of organic solid wastes will aggravate the burden on the environment, therefore, it is significant to transform wastes into carbon‐based materials for sustainable energy utilization. Herein, a kind of hard carbon materials are reported with waste biomass‐foam as the precursor, which can im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Moreover, the reversible specific capacity/plateau capacity of GHC x is significantly lower than that of ZGHC1500. Figure g and Table S4 provide a comparison on the reversible specific capacity/plateau capacity of ZGHC1500 anode with the recently reported hard carbon anodes for SIBs, ,,,,,, demonstrating its leading position.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, the reversible specific capacity/plateau capacity of GHC x is significantly lower than that of ZGHC1500. Figure g and Table S4 provide a comparison on the reversible specific capacity/plateau capacity of ZGHC1500 anode with the recently reported hard carbon anodes for SIBs, ,,,,,, demonstrating its leading position.…”
Section: Resultsmentioning
confidence: 70%
“…Preoxidation is a method for constructing closed pores. Generally, preoxidation can boost the degree of cross-linking of the precursors, which can hinder the orientated growth of graphitic domains during carbonization, thereby constructing more amorphous carbon microstructures and further forming numerous closed pores. ,, However, the number of closed pores constructed by preoxidation strategies is usually limited, which only results in a slight enhancement of low-voltage plateau capacity for hard carbon. Compared to preoxidation, introducing pore-forming agents including hard templates (e.g., nanosized MgO , and ZnO , ), organics (e.g., ethanol and polyethylene glycol), and activation agents (e.g., KOH) is a more direct way to construct closed pores, allowing for the production of high plateau capacity hard carbon anodes in general.…”
Section: Introductionmentioning
confidence: 99%
“…Galvanostatic intermittent titration (GITT) tests were conducted on the composites to investigate the variation in the diffusion behavior of Na + in the discharge curve . According to Figure g, it can be observed that XA-4T-1300 exhibits longer low-voltage plateau regions.…”
Section: Resultsmentioning
confidence: 99%
“…A number of existing pore structural design strategies, such as preoxidation, pore-forming agents, and filling of carbonaceous precursors, can effectively increase the volume of closed pores in disordered carbon materials and enhance the sodium-ion storage capacity . Meng et al obtained phenolic resin-based carbon negative electrodes with a closed pore structure by using ethanol as a pore-forming agent .…”
Section: Introductionmentioning
confidence: 99%